The Relationship between the Implementation of Religious Programs and Students’ Religious and Nationalistic Character - Nugraha, Jaka; Khomah, Isti; Hanifah, Abu; Abdullah, Rifki; Suhartini, Andewi; Ratnasih, Teti (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
This study examines the relationship between the implementation of religious programs and the religious and nationalistic character of students. The implementation of religious programs has the potential to produce a double impact, namely strengthening the moral integrity of individuals while fostering a nationalistic character in students. However, there has been no research that explicitly discusses how nationalistic character values such as loyalty, appreciation of national culture, or willingness to sacrifice are measured or evaluated as a direct impact of these religious programs. This study aims to fill the gap in the existing literature, which is mostly descriptive, qualitative, or observational, by analyzing the relationship between the implementation of religious programs in schools and the formation of students’ religious and nationalistic character. This study is important to empirically prove that strengthening spiritual values can be in line with the spirit of nationalism in the educational environment. The research method used is a quantitative correlation approach. Data collection was conducted through questionnaires to measure the intensity of student participation in religious programs and their level of religious character and nationalism, which were then analyzed using statistical tests in the form of correlation and simple linear regression tests. The results show a positive and significant relationship between the implementation of religious programs and the formation of students’ religious character and nationalism. These findings indicate that the more intensive the implementation of religious programs, the stronger the students’ religious commitment and love for their country, thus refuting the assumption of dualism between the two. Therefore, educational institutions are advised to optimize these programs as a key strategy in producing a generation of students with comprehensive and balanced character.